The Effects of Digital Learning and Compensation On Teacher Performance in Tangerang City - S, Saring (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Teacher performance is important in relation to the quality of education. Compensation is one of the reasons for having motivation to improve. This research method is a quantitative method. Data was collected through filling out questionnaires and interviews. Data processing using SPSS 25. Data variables X1 (compensation), X2 (digital learning) and Y (teacher performance). The sample was 50 teachers in the city of Tangerang, Banten. Compensation influences teacher performance in the city of Tangerang, digital learning influences teacher performance, and compensation and digital learning influences teacher performance. Heads and education managers can provide appropriate compensation, so that teachers are able to perform well and have adequate digital skills.